Impact of preheating environment on microstructural and optoelectronic properties of Cu2ZnSnS4 (CZTS) thin films deposited by spin-coating. (April 2020) - Ahmoum, H.; Chelvanathan, P.; Su'ait, M.S.; Boughrara, M.; Li, G.; Al-Waeli, Ali H.A.; Sopian, K.; Kerouad, M.; Amin, N.
Abstract: This work presents the effects of the preheating environment on the microstructural, compositional, optical, and electrical properties of spin-coating-deposited CZTS thin films. CZTS precursors were prepared using a sol-gel method and deposited by spin-coating; they were subsequently preheated at 150 °C under different atmospheres (air, Ar, and N2 ) prior to sulfurization at 580 °C. X-ray diffraction (XRD) patterns confirmed the formation of crystalline CZTS with different crystallite sizes, while the Raman spectroscopy results showed that the synthesized films are composed of the stannite CZTS phase. CZTS films preheated in Ar and N2 show better crystallinity, larger grains, and improved surface morphology with less oxygen content compared with as-deposited and air-preheated samples. A suitable bandgap is obtained in all samples, with better absorption in Ar and N2 . Notably, lesser surface microstructural inhomogeneity is observed in samples preheated in Ar and N2 atmospheres, which indicates that both of those environments are suitable for the deposition of CZTS materials for application in solar cells. Highlights: As-deposited and CZTS films preheated in air exhibits higher oxygen content. CZTS films preheated in Ar and N2 exhibit higher crystallinity and larger grains. Preheating in Ar and N2 is more suitable compared to normal atmospheric ambient.